Swift Assembly of Adaptive Thermocell Arrays for Device-Level Healable and Energy-Autonomous Motion Sensors - Lu, Xin; Xie, Daibin; Zhu, Kaihua; Wei, Shouhao; Mo, Ziwei; Du, Chunyu; Liang, Lirong; Chen, Guangming; Liu, Zhuoxin (Nano-Micro Letters, 2023)
The evolution of wearable technology has prompted the need for adaptive, self-healable, and energy-autonomous energy devices. This study innovatively addresses this challenge by introducing an MXene-boosted hydrogel electrolyte, which expedites the assembly process of flexible thermocell (TEC) arrays and thus circumvents the complicated fabrication of typical wearable electronics. Our findings underscore the hydrogel electrolyte's superior thermoelectrochemical performance under substantial deformations and repeated self-healing cycles. The resulting hydrogel-based TEC yields a maximum power output of 1032.1 nW under the ΔT of 20 K when being stretched to 500% for 1000 cycles, corresponding to 80% of its initial state; meanwhile, it sustains 1179.1 nW under the ΔT of 20 K even after 60 cut-healing cycles, approximately 92% of its initial state. The as-assembled TEC array exhibits device-level self-healing capability and high adaptability to human body. It is readily applied for touch-based encrypted communication where distinct voltage signals can be converted into alphabet letters; it is also employed as a self-powered sensor to in-situ monitor a variety of body motions for complex human actions. The swift assembly approach, combined with the versatile functionality of the TEC device, paves the way for future advancements in wearable electronics targeting at fitness monitoring and human–machine interfaces. Highlights: 1 The MXene-boosted rapid gelling expedites the assembly of flexible thermocell arrays, overcoming the typical constraint of complicated device fabrication processes. 2 The hydrogel electrolyte can sustain stable thermoelectrochemical performance under various challenging conditions, including large, repeated, and sustained deformations, and multiple cut-healing cycles. 3 The as-assembled thermocell array exhibits device-level self-healing capability and high adaptability to human body, efficiently harvesting low-grade heat for wearable applications.